Layered policy analysis program evaluation using the marginal treatment effect - Ismael Mourifié; Yuanyuan Wan (Centre for Microdata Methods and Practice (cemmap), 2021)
This paper proposes a unified approach to derive sharp bounds on all conventional policy parameters when the instrumental variables (IVs) are potentially invalid. Using a Vine Copula approach, we propose a novel characterization of the identified sets for the marginal treatment effect (MTE) and the policy-relevant treatment effect (PRTE) parameters. Our method has various advantages: First, it explicitly demonstrates how imposing different IV-related assumptions with different credibility levels affects the MTE and PRTE's identified set. Second, it can be used to test model specifications and hypotheses about various imperfect IV-related assumptions. Third, it provides a tractable way to inform policy choices in the presence of uncertainty of the validity of identifying assumptions. Our approach enlarges the MTE framework's scope by showing how it can be used to inform policy decisions even when valid instruments are not available.
Keywords: C12; C14; C21; C26; 330; Desegregated MTE; Vine Copula; Identified Set; Policy-relevant treatment effect; Specification Test